The great debates in entrepreneurship - Kuratko, Donald F.; Hoskinson, Sherry (Bingley, U.K. : Emerald Publishing Limited, 2017)
This volume presents some of the most important 'debates' that exist in the field of Entrepreneurship today. It brings together leading scholars, deriving contributions from special sessions designed by the Global Consortium of EntrepreneurshipCenters (GCEC) to discuss both sides of these 'great debates'. Topics include: "Is the Business Plan Really Dead and Should It Be?", "Does the Lean Start up Deserve all the Hype?", "Entrepreneurial Ecosystem - Weak Metaphor orGenuine Concept?", "Teaching vs. Doing", "Is there a Role for Lecture and Content in Entrepreneurship Education?", "Should Centers Be Controlled Centrally?", and "Is a Bachelor's Degree in Entrepreneurship Worth It?"
Why content and lecture matter in entrepreneurship education -- Keeping it real: the benefits of experiential teaching methods in meeting the objectives of entrepreneurship education -- Is the business plan really dead and should it be?: a case for the lean start-up approach -- Entrepreneurial ecosystems: weak metaphor or genuine concept? -- Gazelle solution vs. portfolio thinking -- Aspiring entrepreneurs should not major in entrepreneurship -- Valuing a Bachelor degree in entrepreneurship: the LMU experience -- Should university entrepreneurship centers be controlled centrally? lessons learned from transitioning from a business school to a centralized center -- B school, E school, or D school: does entrepreneurship program location matter or is it the ecosystem that counts?
Includes bibliographical references and index.
eBooks on EBSCOhost
Keywords: Entrepreneurship; Business planning; Entrepreneuriat; entrepreneurs; Entrepreneurship; Business & Economics -- Entrepreneurship; BUSINESS & ECONOMICS -- Industrial Management; BUSINESS & ECONOMICS -- Management; BUSINESS & ECONOMICS -- Management Science; BUSINESS & ECONOMICS -- Organizational Behavior; Business planning; Entrepreneurship